Love you Alice, Dee
The back of the photo reads, 'Love you Alice, Dee'. Alice is seated with her hands together, and being embraced by a blonde person. They are seated on an orange-brown couch. Behind them are four pillows, two of which have a blue green patter, one that has a pink and red checkerboard pattern, and one that has an illustration of a house.